A Probabilistic Modeling of the Demand and Supply for Rotable Aircraft Components (Case Study: Brake Assembly of Boeing 737-800) - C D W Kuswardani; E Suwondo (Institut Teknologi Bandung, 2020)
Spare parts control is an important factor in every airlines company. The unavailability of the spare parts may affect the airlines operationally, thus a delay and even a cancellation may happen. A common assumption used to calculate spare part requirements is that the demand is stochastic and the supply is constant. But in real operational circumstance, both of those are stochastic. This research develops the spare parts demand and supply model, and the calculation method of service level and safety stock in the bi-variate distribution from a real data of demand and supply of a rotable component. A fit test is conducted to determine the probability density function of the distribution. An analysis is then carried out after implementing the model in a case study. Historical data of brake assembly used in Boeing 737-800 New Generation is used in the case study. The result of this research are a model to determine demand and supply of aircraft spare part components, a method to calculate service level and safety stock for probabilistic model of demand and supply, and the amount of spare parts required for a brake assembly inventory system